A Case of Fatal Agranulocytosis That Developed in a Patient with β-Thalassemia Major Treated with Deferiprone. (1st November 2016) - Mainou, Maria; Kotsiafti, Aggeliki; Klonizakis, Philippos; Soulountsi, Vasiliki; Apostolou, Chrysoula; Psarras, Kiriakos; Vlachaki, Efthymia
Abstract: A 29-year-old male with transfusion-dependent β-thalassemia major (β-TM), splenectomized and on chelation therapy with deferiprone (DFP or L1) due to heart and liver hemosiderosis, presented with high fever and agranulocytosis. Deferiprone was discontinued and a broad spectrum antibiotic therapy was started intravenously. The patient remained febrile and showed no recovery of neutrophil count even after the initiation of granulocyte colony-stimulation factor (G-CSF). After 12 days at the hospital, he developed respiratory failure and was transferred to the intensive care unit (ICU) where he developed multi-organ failure and died 3 days later. To investigate the mechanism of agranulocytosis, bone marrow mononuclear cells of a healthy volunteer were plated on culture dishes, with or without the patient's serum. The observation of colony forming units of progenitor cells in dishes that contained the patient's serum, provided inconclusive explanation of the possible mechanism of DFP-induced agranulocytosis. This is a case of fatal agranulocytosis developing in a patient being treated with DFP, a well recognized but rare complication of this drug. Further studies are required in order to elucidate the possible pathogenic mechanism of agranulocytosis due to DFP and to provide clear guidelines in order to best care for the patient.